Research on Corporate Social Responsibility Reporting - Camelia I. Lungu; Chiraţa Caraiani; Cornelia Dascălu (Amfiteatru Economic Journal, 2011)
The paper aims to revisit the relationship between reporting companies' characteristics and the importance assigned to social and environmental disclosure, using statistical correlations. We conducted a content analysis on the extent of sustainability reports of the largest 50 companies classified by Global Fortune in 2009, in order to address the research hypotheses. Results show that size characteristics measured by assets and revenues cannot be correlated to the extent of Corporate Social Responsibility reports published by companies, but there is a significant negative correlation between change in revenues and return on equity and social and environmental disclosure for the sampled companies.
Keywords: Q56; 330; corporate social responsibility; social and environmental reporting; companies' characteristics; statistical correlations